Comparative Evaluation of the BD Phoenix Yeast ID Panel and Remel RapID Yeast Plus System for Yeast Identification - Michelle L. Grant; Shobha Parajuli; Raquel Deleon-Gonsalves; Raghava Potula; Allan L. Truant (Canadian Journal of Infectious Diseases and Medical Microbiology)
Becton Dickinson Phoenix Yeast ID Panel was compared to the Remel RapID Yeast Plus System using 150 recent clinical yeast isolates and the API 20C AUX system to resolve discrepant results. The concordance rate between the Yeast ID Panel and the RapID Yeast Plus System (without arbitration) was 93.3% with 97.3% (146/150) and 95.3% (143/150) of the isolates correctly identified by the Becton Dickinson Phoenix and the Remel RapID, respectively, with arbitration.